Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 42. Beitrag. Diptera: Sciomyzidae. - Rozkošny, Rudolf (Contributions to Entomology = Beiträge zur Entomologie, 1965)
The present paper evaluates the material on the Sciomyzidae family collected in the expedition to Albania by Deutsches Entomologisches Institut. It consisted of 134 specimens of 6 species, 5 of which were new in Albania and one species (Pherbellia scutellaris Von Roser) new even in the whole Balkan region. A list of all Sciomyzidae known from Albania (a total of 10 species) is given, followed by a short historical survey of the study of the Sciomyzidae of the Balkan countries and a table of their distribution on the Balkan peninsula.